Factors associated with adherence in patients with type 2 diabetes mellitus - Świątoniowska, Natalia; Dudek, Krzysztof; Szymczyk, Anna; Jankowska-Polańska, Beata (Journal of Education, Health and Sport, 2018)
Introduction. Only 50 - 75% of patients surveyed adhere to therapeutic recommendations in the treatment of chronic diseases. It is estimated that half of the patients discontinue therapy after one year from the start of treatment. Failure to comply with therapeutic recommendations often leads to complications of diabetes. New methods are now being sought to help diabetics adhere to the recommendations of the therapeutic team. According to the World Health Organization, interventions to improve adherence have a greater impact on health than the development of treatment. The aim of the study was to analyze the degree of adaptation to the therapeutic recommendations of patients with type 2 diabetes. Material and methods. 150 patients (96 women) 65.2 ± 11.8 years of age who were treated for exacerbation of type 2 diabetes were examined with their own questionnaire regarding compliance with the therapeutic recommendations and a standardized HBI (Health Behavior Inventory) questionnaire to assess health behaviors. Results. A high degree of compliance with pharmacological recommendations was presented by 30%, the average 42,7%, and low 27,3% patients. High level of adherence was presented by people aged 50-69 (p<0.001), higher education (p=0.042), in a relationship (p=0.026), living in the countryside (p=0.029). People with a high level of compliance with pharmacological recommendations more often followed behavioral recommendations regarding weight reduction (62.2% vs. 23.4% vs. 31.7%), physical activity (71.1% vs. 45.3% vs. 46.3%) and daily weight control 33.3% vs. 17.2% vs. 4.9%). In the comparative analysis of the level of adherence, depending on the selected variables, it was observed that the higher level of compliance was for people who were diagnosed with comorbidities (compliance with the recommendations 6.6 vs. 5.1 in people without additional diseases), in non-smokers than in those who smoked tobacco ( 6.9 vs. 6.1), in subjects with hemoglobin HbA1C  7% than in HbA1C patients> 7% (7.0 vs. 6.6). The level of adherence to recommendations was the lowest in patients treated with the combination regimen (tablets+insulin; p=0.024). High level of health behaviors was presented more often by women compared to men (108 vs. 103), older people compared to younger ones (age 60-69 HBI=109.1 vs. age up to 49 years HBI=93.3), pensioners compared to economically active people or unemployed (108.3 vs. 101.1 vs. 92.3). In multivariate analysis, the independent predictors of adherence to pharmacological therapeutic recommendations are the absence of co-morbidities and older age (β=0.212, p=0.005). Conclusions. Patients with diabetes have a moderate level of adherence and the compliance with health behaviors. An independent predictor which has a positive influence on the HBI is the old age (the older the patient, the better the level of adherence). The predictor which reduced the level of adherence and the HBI was the absence of comorbidities.